Beliefs and Portfolios: Causal Evidence - Beutel, Johannes; Weber, Michael (Review of Financial Studies, 2026)
Abstract We causally test alternative theories of expectation formation. Using a randomized information experiment we show overreaction is a key feature of individuals’ return expectations, and individuals’ response to the price-earnings ratio is opposite of academic consensus. Our evidence is inconsistent with standard models of expectation formation, but subjective mental models that deviate from objective benchmarks can jointly explain the updating behavior in the experiment, the link between individuals’ prior perceptions and expectations, and the heterogeneity of updating. Conditional on their beliefs, individuals’ sensitivity of equity shares in a hypothetical portfolio choice experiment is consistent with the standard Merton model.